Efektivitas Bursa Kerja Khusus Dalam Menyalurkan Alumni Sekolah Menengah Kejuruan Unggul Negeri 2 Banyuasin III Kabupaten Banyuasin Ke Dunia Usaha, Dunia Industri Dan Dunia Kerja - Yulianti, Eni; Nawawi, Effendi; Asteriniah, Femi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
The Central Statistics Agency (BPS), 2021 reported that the majority of unemployment in Indonesia comes from the Vocational High School (SMK) graduate group. The unemployed population with the final education level of SMK reached 11.13% in August 2021. Most SMK graduates want to work immediately, but are not absorbed in the business world and the industrial world. The problem raised in this study is that there are still many alumni of SMK Unggul Negeri 2 Banyuasin III who have not been absorbed in the dudika. The purpose of this study was to determine the number of alumni of SMK Unggul Negeri 2 Banyuasin III who were absorbed and not absorbed in the dudika. This type of research includes qualitative research with the research approach used is the effectiveness approach developed by Richard M. Steer including research, input, process, and product. the effectiveness of the special labor exchange in channeling alumni of smk unggul negeri 2 banyuasin 3 to the business world, the industrial world and the world of work (dudika) has been effective as evidenced by an increase in the absorption of alumni in dudika. from the tracer study obtained data on alumni of smk unggul negeri 2 banyuasin 3 for 2020 alumni who work are: 12/69 = 17,3 %. Data for 2021 which alumni who work are 12/69 = 17.3% and 22/169 = 13.0%, data for 2022 alumni who work are: 22/69 = 31.8% - 44/169 = 26.0%, and 52/184 = 29.3%. Based on the data above, the percentage of alumni who work has increased.